2015
DOI: 10.1016/j.physa.2014.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling correlations between financial variables and topological metrics of trading networks: Evidence from a stock and its warrant

Abstract: h i g h l i g h t s• We construct and investigate time series of security trading networks. • Correlation relationships are uncovered between trading network metrics and financial variables. • The structure of trading networks contains rich information about the dynamics of securities. a b s t r a c t Traders develop and adopt different trading strategies attempting to maximize their profits in financial markets. These trading strategies not only result in specific topological structures in trading networks, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…-Financial markets evolve in a selforganized manner with the interacting elements forming complex networks at different levels, including international markets [1][2][3][4], individual markets [5][6][7][8], and security trading networks [9][10][11][12][13][14][15][16]. There are well-documented stylized facts of stock return time series within individual markets unveiled by the random matrix theory (RMT) analysis [6,17]: (1) The largest eigenvalue reflects the market effect such that its eigenportfolio returns are strongly correlated with the market returns; (2) Other largest eigenvalues contain information of industrial sectors; and (3) The smallest eigenvalues embed stock pairs with large correlations.…”
mentioning
confidence: 99%
“…-Financial markets evolve in a selforganized manner with the interacting elements forming complex networks at different levels, including international markets [1][2][3][4], individual markets [5][6][7][8], and security trading networks [9][10][11][12][13][14][15][16]. There are well-documented stylized facts of stock return time series within individual markets unveiled by the random matrix theory (RMT) analysis [6,17]: (1) The largest eigenvalue reflects the market effect such that its eigenportfolio returns are strongly correlated with the market returns; (2) Other largest eigenvalues contain information of industrial sectors; and (3) The smallest eigenvalues embed stock pairs with large correlations.…”
mentioning
confidence: 99%
“…It contributes to the field of market surveillance. Another work is to study the correlations between market indicators and network topological metrics to unveil how the trading behaviors affect the market performance [25]. It contributes to the behavioral finance research.…”
Section: Complex Network Analysis On Stock Marketsmentioning
confidence: 99%
“…Li [21] HSI fluctuation patterns Important topological nodes Hong Kong stock market Bakker [22] Investment behavior of trust traders Impacts of trust networks on the stabilization of market NA Jiang [23] Trading behavior Power-law degree distribution Shenzhen stock exchange Jiang [24] Trading behavior Abnormal motifs Shenzhen stock exchange Li [25] Trading behavior Correlations between financial variables and network metrics A specific stock…”
Section: Studiesmentioning
confidence: 99%
“…Caraiani (2012) constructed the network using the Pearson correlation coefficient as the edge information in the European stock market and found that the stock network shows scale-free features and the clustering coefficients show multiple fractal features. Li et al (2015) used the Pearson correlation coefficient as a trading channel for Baosteel's equity information and found that there are strong simultaneous correlations between the topological metrics of trading networks that characterize the patterns of order execution and the financial variables for the stock and its warrant. Chen, Luo, Sun, and Wang (2015) constructed the network using the Pearson correlation coefficient as the edge information on the SSE stock market in China and found that there is a correlation between the industry's proximity and industry return, as well as between stock centre and stock returns.…”
Section: Introductionmentioning
confidence: 99%